The Influences of Products’ Attribute, The Brand Image and The Price Toward The Purchase of The Prime Axis Internet Card (A Study of Users’ Cards of Prime Axis Internet of The Students’ At Muhammadiyah University of Purwokerto) - Wahyuni, Cici (International Conference of Moslem Society, 2018)
This research aimed to find out the factor attributes of products, promotions, brand image and price toward the purchase of Prime Axis Internet card done by the students of Muhammadiyah University of Purwokerto. The data collection technique implemented purposive sampling, addressing the consumers who did the purchases using the card of Prime Axis Internet. There were 107 respondents as the samples involved in this study. The Methods used in this research was regression analysis method that included validity and reliability test, multiple linear regression analysis, determination test, F-test and t-test. The results of the research was proven by using multiple analysis that indicated a variable product attributes, brand image, positive price and significant effect toward decision-making to do the purchase, positive and influential promotion variables were not significant to influence the purchasing decisions. While in line with the attributes of products; the promotions, brand image, and price showed a positive and significant effect toward the purchasing decisions.